2015
DOI: 10.1074/jbc.m115.690354
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Approach for Analysis of the DNA Damage Response in Mammalian Cells

Abstract: Background: Current assays for monitoring DNA excision repair in vivo lack sensitivity. Results: An in vivo excision assay can be used to examine repair of DNA damage induced by many carcinogens and anti-cancer agents. Conclusion: This methodology provides a sensitive assay for studying nucleotide excision repair in vivo. Significance: Repair of a broad range of DNA lesions can be readily observed in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 41 publications
3
39
0
Order By: Relevance
“…However, there is currently no in vitro excision repair assay for plant nucleotide excision repair. We therefore adapted the in vivo excision assay that we recently developed in our laboratory for studying nucleotide excision repair in mammalian cells in vivo (12)(13)(14). In this assay, cells are lysed at various time points following UV irradiation and the excised oligonucleotide products of nucleotide excision repair are isolated by immunoprecipitation with antibodies against either the repair factor TFIIH (because the excised oligonucleotide is released in a complex with the core repair factor TFIIH) or against specific UV photoproducts (12, 20).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is currently no in vitro excision repair assay for plant nucleotide excision repair. We therefore adapted the in vivo excision assay that we recently developed in our laboratory for studying nucleotide excision repair in mammalian cells in vivo (12)(13)(14). In this assay, cells are lysed at various time points following UV irradiation and the excised oligonucleotide products of nucleotide excision repair are isolated by immunoprecipitation with antibodies against either the repair factor TFIIH (because the excised oligonucleotide is released in a complex with the core repair factor TFIIH) or against specific UV photoproducts (12, 20).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, there have been no mechanistic studies on plant nucleotide excision repair, although it is known that plants can remove cyclobutane pyrimidine dimers (CPDs) and pyrimidine pyrimidone photoproducts [(6-4)PPs] in a photolyase-independent manner (6,10,11), presumably by nucleotide excision repair. Here, we have used an Arabidopsis cell line and the in vivo excision assay recently developed in our laboratory (12)(13)(14) to demonstrate that Arabidopsis removes these photoproducts by dual incisions in a manner that is virtually identical to human nucleotide excision repair.…”
mentioning
confidence: 99%
“…Thus, the presence of DNA oligonucleotides of this length in complex with TFIIH is a defining feature of the human nucleotide excision repair system and can be used to monitor excision repair in cultured cells. Moreover, we have shown that this general methodology is useful for monitoring excision repair kinetics in response to a wide variety of DNA-damaging agents that generate DNA adducts that are targeted by the nucleotide excision repair system (35).…”
Section: Resultsmentioning
confidence: 99%
“…BPDE preferentially forms bulky covalent DNA adducts at N2 position of guanines and causes mutations if these BPDE-deoxyguanosines (BPDE-dGs) are not efficiently eliminated by nucleotide excision repair (3). Various methods of varying resolutions have been developed for mapping DNA damage and repair genome-wide (4)(5)(6)(7)(8)(9). We previously reported a method, termed excision repair-sequencing (XR-seq), for mapping nucleotide excision repair (6).…”
mentioning
confidence: 99%